Pedagogical laboratories as teaching didactics in rural contexts - Jaller Quintero, Abid Antonio (2025)
Education in all countries is the key to the development of societies and human beings. Latin America and the Caribbean presents challenges to solve various issues that affect the quality of education. The rural school develops a set of strategies to promote the development of education for boys and girls. However, more efforts are still required on the part of educational institutions, teachers and the community in general. The article “Pedagogical laboratories as teaching didactics in rural contexts" identifies and describes these strategies as a contribution to the teaching-learning process in educational institutions, and the promotion of harmonious, collaborative and inclusive environments. It also explores the implementation of innovative teaching methods, which favor the development of pedagogical laboratories in teaching didactics in educational quality in rural contexts. The review is based on the collection and documentary analysis of didactic strategies applied in rural educational contexts, particularly those focused on pedagogical laboratories. The review shows that didactic strategies based on pedagogical laboratories contribute significantly to school coexistence within rural institutions. These didactics promote an inclusive, collaborative, respectful learning environment and integral development of students. It underlines the importance of adapting educational strategies to the specific needs of rural communities, offering key tools for education policy makers.